The issue of family education in creative heritage of representatives of the foreign pedagogical thought - Milash, O. (Problems of Engineer-Pedagogical Education, 2019)
The article analyzes historical and pedagogical sources in оrder to identify the origins and further development of the issue of family education in the history of foreign pedagogy. It is established that Aristotle was at the root of researching the issue under study. The paper characterizes his views on the role of the family in the formation of a child's personality, describes the main tasks and methods of early upbringing of children in privileged families; proves that the main task of family education from an early age consisted, according to the thinker‟s beliefs, in development of moral values, while formation of a habit of «noble deeds» was considered its most positive outcome; outlines the factors and the most effective methods of children‟s moral education in the family; and also mentions Aristotle‟s main requirements for family education as a basis of children‟s moral development. The views of the most vivid Renaissance representatives of the pedagogical thought, including L. B. Alberti, D. E. Roterodamus, M. Montaigne and others are considered; it is proved that the goal of education, as humanists-educators believed, was comprehensive and harmonious development of a child in accordance with the main areas of upbringing (mental, physical, and moral); the main requirements of humanists for family education are singled out; the conditions and methods of upbringing children in the family are described. The theory of John Amos Comenius on the maternal school as the first step in upbringing and education of children from birth to six years is analyzed; the purpose and objectives of children's upbringing are defined; the content and methodology of preschool education are determined according to the peculiarities of psychological development of preschool children outlined by J.A. Comenius; the most effective methods of moral education are singled out and the advantages of parents‟ «personal example» are stated; it is proved that J.A. Comenius considered the feeling of love to be the most important factor in the formation of a moral personality in the family; the directions of mental development of children are determined; the content of subjects for studying at the maternal school is specified and characterized; the skills and abilities needed to be formed at the maternal school as the basis for children‟s further school education are analyzed. The methods and techniques for the development of children‟s emotional and aesthetic experiences are defined.